Molecular analyses on Neospora caninum-triggered NETosis in the caprine system. (July 2017) - Villagra-Blanco, R.; Silva, L.M.R.; Gärtner, U.; Wagner, H.; Failing, K.; Wehrend, A.; Taubert, A.; Hermosilla, C.
Abstract: Neospora caninum is an obligate intracellular protozoan parasite causing serious reproductive disorders in large and small ruminants worldwide. Polymorphonuclear neutrophils (PMN) react against multiple invading pathogens through different mechanisms including the release of neutrophil extracellular traps (NETs). Here, in vitro interactions of caprine PMN and N. caninum tachyzoites were studied. Scanning electron microscopic- and immunofluorescence-analyses demonstrated that caprine PMN undergo NETosis upon contact with tachyzoites of N. caninum, extruding filaments that entrap parasites. Detailed co-localization studies of N. caninum tachyzoite-induced NETs revealed the presence of PMN-derived DNA being decorated with histones (H1, H2A/H2B, H3, H4) and neutrophil elastase (NE) corroborating the molecular characteristics of classical mammalian NETs. As a new result for parasite-induced NETosis, we identified pentraxin and cathepsin B in N. caninum -triggered NETs. Nonetheless, functional inhibition assays revealed that during caprine NET formation triggered by N. caninum different molecular signaling pathways are induced, when compared to other apicomplexan parasites or host species. As such, N. caninum -induced NETosis appears to be influenced by MPO but independent of NADPH oxidase, SOCE, ERK1/2 and p38 MAPK activities. Furthermore, the inhibition of PMN autophagy via blockage of the PI3K-mediated signaling pathway failed to influence tachyzoite-induced NETosis. Since N. caninum -tachyzoites induced caprine NETosis, this effector mechanism should be considered as an early host immune response during acute caprine neosporosis. Highlights: Caprine PMN-stimulated NETs were rapidly generated upon contact with N. caninum. Histones, neutrophil elastase, myeloperoxidase, pentraxin and cathepsin B were involved in N. caninum -triggered NETs. N. caninum -induced NETosis in goats is a NOX-, SOCE-, ERK1/2- and p38 MAPK –independent process. Suppression of PMN autophagy via PI3K-blockage failed to influence NETosis.